1994
DOI: 10.1073/pnas.91.13.6040
|View full text |Cite
|
Sign up to set email alerts
|

Human and rat TR4 orphan receptors specify a subclass of the steroid receptor superfamily.

Abstract: We have identified a member of the steroid receptor superfamily and cloned it from human and rat hypothalamus, prostate, and testis cDNA libraries. The open reading frame between first ATG and terminator TGA can encode 615 (human) and 596 (rat) amino acids with calculated molecular mass of67.3 (han) and 65.4 (rat) kDa. The amino acid sequence of this protein, called TR4 orphan receptor, is closely related to the previously identified TR2 orphan recep-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
139
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 20 publications
(20 reference statements)
4
139
0
Order By: Relevance
“…The testicular receptor 4 (TR4) was first cloned from prostate and testis cDNA libraries and is highly homologous to the TR2 nuclear receptor [1]. The molecular structure analyses indicated that TR4 belongs to the nuclear receptor superfamily that may control the expression of target genes involved in developmental, physiological, and behavioral responses from the cellular level to that of the whole organism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testicular receptor 4 (TR4) was first cloned from prostate and testis cDNA libraries and is highly homologous to the TR2 nuclear receptor [1]. The molecular structure analyses indicated that TR4 belongs to the nuclear receptor superfamily that may control the expression of target genes involved in developmental, physiological, and behavioral responses from the cellular level to that of the whole organism.…”
Section: Introductionmentioning
confidence: 99%
“…The structural features common to nuclear receptors include those required for ligand binding, dimerization, DNA binding, and transactivation. TR4 has been an orphan nuclear receptor without an identified ligand since it was cloned in 1994 [1]. Recently, Xie et al .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that these nuclear receptors may play important roles in viral transcription. The detailed mechanisms of how the core promoter is differentially regulated by these nuclear receptors remain unclear.The testicular orphan receptor 4 (TR4) (NR2C2) is an orphan member of the nuclear receptor superfamily (15)(16)(17). This family includes classic steroid hormone receptors, the thyroid hormone receptor, the retinoid receptors, and many nuclear orphan receptors whose physiological ligands have not been identified (18).…”
mentioning
confidence: 99%
“…The testicular orphan receptor 4 (TR4) (NR2C2) is an orphan member of the nuclear receptor superfamily (15)(16)(17). This family includes classic steroid hormone receptors, the thyroid hormone receptor, the retinoid receptors, and many nuclear orphan receptors whose physiological ligands have not been identified (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation